PENGARUH PROMOSI JABATAN TERHADAP SEMANGAT KERJA KARYAWAN TETAP PADA PERUSAHAAN DAERAH AIR MINUM TIRTA OGAN DI BATURAJA - Hema Malini; Safaruddin; Selvi Desfarina (Pojok Publisher, 2024)
A person tends to work enthusiastically if they get satisfaction from their work because job satisfaction is the key to supporting the company's goals. The assessment for job promotion specifically for subordinates is only assessed by the leader at the Tirta Ogan Regional Drinking Water Company in Baturaja. The assessment for job promotion for several employees who have worked for a long time (over 4-5 years) carried out by the board of directors is only as one of the requirements (formality) to increase job promotion. This has an impact on the declining work spirit of employees. This research method is a descriptive quantitative method. From the simple linear regression equation, the correlation between the job promotion variable (X) and work spirit (Y) is 0.693 which has a strong correlation. The R Square of 0.481, the contribution of the job promotion variable (X) to work spirit (Y) is 48.1%. While the remaining 51.9% is influenced or varied by other variables not examined in this study. The results of the calculation of the large t-test obtained a job promotion (X) of 7.138 and 2.00404, then > (2.00404) meaning that H0 is rejected and Ha is accepted, meaning that there is a significant influence between job promotion and the work enthusiasm of Permanent Employees at the Tirta Ogan Regional Drinking Water Company in Baturaja.